So near, so far, so what is social distancing? A fundamental ontological account of a mobile place brand - George Rossolatos (Place Branding and Public Diplomacy, 2020)
This paper offers a social phenomenological reading of the globally binding practice of `social distancing' in light of the precautionary measures against the spreading of the Covid-19 virus. Amid speculation about the far-reaching effects of temporarily applicable measures and foresights about the advent of an ethos that has been heralded by the media as the `new normal', the ubiquitous phenomenon of social distancing calls for a fundamental ontological elucidation. The purported hermeneutic that is situated in the broader place branding and experiential marketing literatures places Covid-19 in the shoes of Being, and, therefore, imagines how Being would behave ontologically if it were a virus. By arguing that the virus does operate like Being, five theses are put forward as experiential interpretive categories with regard to the ontological status of Covid-19. The adopted approach makes the following contributions to the extant literature: First, it addresses a wholly new phenomenon in place branding, namely a pre-branded place whose meaning is non-negotiable, globally applicable and seemingly equivalent to pure void. Second, it advances the application of phenomenological research in place branding and experiential consumption by highlighting the aptness of the so far peripheral (in the marketing discipline) strand of Heideggerian fundamental ontology. Third, it extends the meaning of place in the place branding literature, by showing how spatialization is the outcome of temporalization, in line with the adopted phenomenological perspective.
Keywords: 330; Social distancing; Place branding; Experiential consumption; Covid-19; Social phenomenology; Fundamental ontology; Rhetoric